Aerothermal performance evaluation of a tube mounted with broken V-ribbed twisted tape: Effect of forward/backward arrangement - Chuwattanakul, V.; Wongcharee, K.; Ketain, P.; Chamoli, S.; Thianpong, C.; Eiamsa-Ard, S. (My University, 2023)
An experimental investigation on the aerothermal performance of a heat exchanger tube equipped with newly designed broken V-ribbed twisted tapes (B-VRT), was carried out. In the present work, the heat transfer intensification by a B-VRT can be attributed to greater mixing caused by two flow characteristics: 1) longitudinal vortices from the ribs and 2) swirling flow from the twisted tape. The B-VRT with rib attack angles (α) of 45°, 60°, 75°, and 90°, were tested using air as the test fluid. The experimental results of the tube with B-VRTs in a forward/backward arrangement were compared to those of a plain tube alone and a tube with typical twisted tapes (TT) for Reynolds numbers between 6,000 and 20,000. The results indicated that the tube with the B-VRT having forward facing ribs with α = 45° gave the best performance with Nusselt number ratio (Nu/Nup) of 2.27, a friction factor (f/fp) of 4.4, and an aerothermal performance factor (APF) of 1.38. For the range investigated, the B-VRT offered up to 31.9% higher Nusselt numbers than TT. The B-VRT with the smallest rib attack angle (α) of 45° offered higher aerothermal performance factors than the ones with rib attack angles (α) of 60°, 75°, and 90° by approximately 6.85%, 12.99%, and 20.2%, respectively. The results of the B-VRT with optimum geometry (α = 45°) were benchmarked against those reported in similar published papers. Evidently, the aerothermal performance factors the B-VRT were superior to those of most of other tube inserts, especially at low Reynolds numbers. Finally, within the range of parameters (α, y/W and Re) taken into consideration in this study, correlations of Nu and f were developed to estimate the heat transfer and pressure drop. The correlations for Nu, f, and APF showed acceptable prediction accuracies, with respective deviations of ±4%, ±5.4%, and ±4%.
Keywords: Aerothermal performance factor; Broken V-Ribbed twisted tape; Enhanced heat transfer; Typical twisted tape